Institutionalization of management accounting rules and routines in a private educational foundation in Santa Catarina: institutional approach of the Brazilian third sector - Renícia Maria Innocenti; Rogério João Lunkes; Valdirene Gasparetto (Revista Ambiente Contábil, 2021)
Purpose: To verify the change of rules and routines of management accounting of a third sector organization in the light of the Old Institutional Economy (OIE).